The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/1471-2350-10-118
|View full text |Cite
|
Sign up to set email alerts
|

Emilin1 gene and essential hypertension: a two-stage association study in northern Han Chinese population

Abstract: BackgroundElastogenesis of elastic extracellular matrix (ECM) which was recognized as a major component of blood vessels has been believed for a long time to play only a passive role in the dynamic vascular changes of typical hypertension. Emilin1 gene participated in the transcription of ECM's formation and was recognized to modulate links TGF-β maturation to blood pressure homeostasis in animal study. Recently relevant advances urge further researches to investigate the role of Emilin1 gene in regulating TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In fact, recent association studies have suggested that specific haplotypes of EMILIN1 are useful genetic markers of essential hypertension in Japanese men and that the interaction of age and genotype variation of specific single nucleotide polymorphisms might increase the risk of hypertension in a northern Han Chinese population. 6,7 Here, we have addressed the question of the cellular context of Emilin-1 activity using a phenotype rescue approach by expressing the protein in either ECs or VSMCs or in all cells of the arterial wall of Emilin1 −/− mice. Our results indicate that Emilin-1 expression in VSMCs is specifically required for BP control and further clarify that the protein regulates the arteriolar myogenic response through TGF-β.…”
mentioning
confidence: 99%
“…In fact, recent association studies have suggested that specific haplotypes of EMILIN1 are useful genetic markers of essential hypertension in Japanese men and that the interaction of age and genotype variation of specific single nucleotide polymorphisms might increase the risk of hypertension in a northern Han Chinese population. 6,7 Here, we have addressed the question of the cellular context of Emilin-1 activity using a phenotype rescue approach by expressing the protein in either ECs or VSMCs or in all cells of the arterial wall of Emilin1 −/− mice. Our results indicate that Emilin-1 expression in VSMCs is specifically required for BP control and further clarify that the protein regulates the arteriolar myogenic response through TGF-β.…”
mentioning
confidence: 99%
“…The present study in Singaporean Chinese subjects (mean age below 50 years) observed a similar association of EH with rs2011616 (Table 3) as found in northern Han Chinese subjects aged o50 years. 28 Similarly, the Japanese study by Shimodaira et al in hypertensive patients and controls without FHH showed a genotypic association of EH with the G allele (AG/ GG genotype) of rs2011616. 15 The present study also detected an association of the G allele of rs2011616 with hypertension.…”
Section: Discussionmentioning
confidence: 90%
“…We identified rs7424556 after screening for genetic variants. Shen et al 28 and Shimodaira et al 15 might have missed rs7424556, because they selected their SNPs from public databases, such as those of the International HapMap Project and the NCBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several genes were reported to be involved in blood pressure regulation and the susceptibility to hypertension modulated by age (Dao et al, 2005;Lunetta et al, 2007;Shen et al, 2009;Shi et al, 2009). Furthermore, the statistical analysis strategy of age-genetic effects can prevent potential confounding bias modified by age-varying characteristics (Lunetta et al, 2007;Lasky-Su et al, 2008;Percy et al, 2009).…”
Section: Discussionmentioning
confidence: 94%